TRANSFORMATION OF EDUCATIONAL PROCESS MANAGEMENT IN HIGHER AND VOCATIONAL EDUCATION BASED ON DIGITAL PLATFORMS AND SMART TECHNOLOGIES (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the transformation of educational process management in higher and vocational education based on digital platforms and smart technologies. The rapid development of digital transformation and smart technological solutions has created new opportunities for improving academic management, enhancing teaching efficiency, and optimizing educational processes. The study analyzes modern approaches to the integration of digital platforms, learning management systems, artificial intelligence, and educational data analytics into academic administration. The research demonstrates that smart technologies contribute to the automation of educational management, support data-driven decision-making, and enable personalized learning pathways. The article identifies key directions for the development of smart digital educational ecosystems aimed at improving the quality of educational services and strengthening professional competencies required in the digital economy. The findings provide practical recommendations for implementing digital platforms and smart technologies in educational process management.